Efectos de la combinación de micorrizas más ácidos húmicos sobre el comportamiento agronómico del cultivo de maíz (Zea mays L.), en la zona de Babahoyo - Flores Leturne, Hamilton Vladimir (2019)
IX. SUMARY The present experimental work was carried out on the grounds of the experimental farm of the faculty of agricultural sciences of the Technical University of Babahoyo, Province of Los Ríos, located at Km 7½ of the Babahoyo - Montalvo highway with the geographic coordinates of 658802 E and 9796957 N. The proposed objectives were: To determine the effect of the combination of mycorrhizas and humic acids on the agronomic behavior of the corn crop; establish the treatment with the greatest increase in crop grain yield and perform the economic analysis in relation to the benefit / cost. Seed of the SOMMA hybrid was used as seed material. The treatments were composed of different products based on mycorrhiza (Mycor) at doses of 0.5 and 1 L / ha, plus humic acids (Humus 12 %, Humus 27 % and Ihumix XD) in doses of 2, 3, L / ha and 30, 40 Kg / ha; plus an absolute witness without application of the aforementioned products. The experimental design of Factorial Designs AXBXC + 1 was applied with thirteen treatments and three repetitions. The comparison of the means was made with the Tukey test 5% probability. The highest plant height was presented with the application of Mycor and Humus 12 % interaction in doses of 0.5 and 3 L / ha, with an average of 226.47 cm; the highest height at the insertion to the first ear was evidenced by the application of Mycor and Humus 12 % interaction in doses of 0.5 and 2 L / ha, with an average of 127.2, the days of flowering presented the interaction of Mycor and Ihumix XD at a dose of 0.5 and 40 Kg / ha, with an average of 61.33, the days of harvest the highest average was shown by the interaction of Mycor and Humus 12 % at a dose of 1 and 3 L / ha with 127.67, the length of the cob showed the interaction of Mycor and Humus 12 % at a dose of 0.5 and 2 L / ha presented the highest average with a value of 19.37, in terms of the weight variable of 100 grains. presented values indicate that the interaction of Mycor and Humus 12 % at a dose of 0.5 and 2 L / ha presented the highest average of 45.33, the performance obtained to the interaction of Mycor and Humus 12 % at a dose of 1 and 2 L / have presented an average of 6491 which makes it the highest value.